A pilot study of a longitudinal mindfulness curriculum in undergraduate medical education - MacLean, Heather; Braschi, Emelie; Archibald, Douglas; Sanchez-Campos, Millaray; Jebanesan, Danusha; Koszycki, Diana; Gonsalves, Carol (Canadian Medical Education Journal, 2020)
Background: To support student well-being, a mindfulness curriculum in undergraduate medical education was launched at our university in 2014. We describe the program and report 3-year results. Methods: Medical students responded to online questionnaires on mindfulness (Freiburg Mindfulness Inventory), empathy (Jefferson Scale of Physician Empathy), resilience (Connor-Davidson Resilience Scale) and perceived stress (Perceived Stress Scale) and were surveyed for demographics, home practice, and subjective experience at curriculum launch and yearly for 3 years. Results: In respondents, high stress (19.2 (SD=6)) and low resilience (71.2 (SD=12.5)) scores were seen throughout training. Scores for mindfulness correlated positively with those for empathy (r=.217 p<0.01) and resilience (r=.539, p<0.01), and negatively with stress scores (r=-.380, p<0.01). While overall scale scores did not statistically change after curriculum implementation, statistically significant increases were seen in mindfulness (12%, p=0.008), empathy (5%, p=0.045), and resilience scores (12%, p=0.002) with a trend toward lower stress scores (8%, p=0.080) in respondents who felt they applied the curriculum principles. Two hours of reported home practice per week was associated with statistically significant changes (14% increased mindfulness scores p<0.001; 6% increased empathy scores p<0.001, 10% increased resilience scores p=0.003; 11% decreased stress scores p= 0.008). Despite positive program evaluations for both mandatory and elective sessions, student attendance at elective sessions was low. Conclusion: A mindfulness curriculum integrated into formal undergraduate medical education is feasible. Benefits may be confined to those students who apply curriculum principles and practice regularly. Further study is needed.